Pengaruh Literasi Keuangan dan Inklusi Keuangan Terhadap Kinerja Usaha Mikro, Kecil, dan Menengah (UMKM) - Senda Yunita Leatemia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to examine the effect of financial literacy and financial inclusion on the performance of MSMEs. This research is a quantitative research that uses primary data with data collection techniques through questionnaires that are distributed directly to MSMEs in Aru Islands Regency, Maluku. Data processing was carried out using multiple linear regression analysis. The results in this study indicate that financial literacy has a positive effect on the performance of MSMEs and financial inclusion does not affect the performance of MSMEs. Implications of the research for MSMEs who have the ability and knowledge to manage finances effectively wiil be able to improve the performance of the businesses they run and the result of this research are used as input for MSMEs to pay attention to financial literacy and financial inclusion to improve the current performance.